Successful A2 to B Deceased Donor Kidney Transplant after Desensitization for High-Strength Non-HLA Antibody Made Possible by Utilizing a Hepatitis C Positive Donor. (13th March 2020) - Karpel, H. Charli; Ali, Nicole M.; Lawson, Nikki; Tatapudi, Vasishta S.; Friedlander, Rex; Philogene, Mary Carmelle; Montgomery, Robert A.; Lonze, Bonnie E.
Abstract : Desensitization using plasma exchange can remove harmful antibodies prior to transplantation and mitigate risks for hyperacute and severe early acute antibody-mediated rejection. Traditionally, the use of plasma exchange requires a living donor so that the timing of treatments relative to transplant can be planned. Non-HLA antibody is increasingly recognized as capable of causing antibody-mediated renal allograft rejection and has been associated with decreased graft longevity. Our patient had high-strength non-HLA antibody deemed prohibitive to transplantation without desensitization, but no living donors. As the patient was eligible to receive an A2 ABO blood group organ and was willing to accept a hepatitis C positive donor kidney, this afforded a high probability of receiving an offer within a short enough time frame to attempt empiric desensitization in anticipation of a deceased donor transplant. Fifteen plasma exchange treatments were performed before the patient received an organ offer, and the patient was successfully transplanted. Hepatitis C infection was treated posttransplant. No episodes of rejection were observed. At one-year posttransplant, the patient maintains good graft function. In this case, willingness to consider nontraditional donor organs enabled us to mimic living donor desensitization using a deceased donor.